2019
DOI: 10.12944/crnfsj.7.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Nutrient intake and Dietary Diversity among Female Residential Students of Bangladesh

Abstract: The efficacy of nisin (25-75 ppm) and effect of storage time on quality attributes of micro-filtered coconut water during refrigerated storage (4°C) for 8 days was investigated in terms of total viable counts, colour, turbidity and overall sensory acceptance. All treatments significantly retarded the bacterial growth in coconut water during storage when compared to the control sample (p < 0.05). The samples treated with 50 and 75 ppm nisin had significantly lower aerobic microbial counts than the control (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
(11 reference statements)
3
9
0
Order By: Relevance
“…Correlation coefficients (r) between DDS, NAR, and MAR of the 14 micronutrients were significant. This collaborate findings in earlier studies that diversity in the diet is positively associated with nutrient adequacy among women of reproductive age (Acham et al 2012;Arimond et al 2010;Drewnowski et al 1997;Foote et al 2004;Hjertholm et al 2019;Lee et al 2013;Mirmiran et al 2006;Nguyen et al 2018;Ogle et al 2001;Ruel 2003;Sultana et al 2019;Torheim et al 2003;Torheim et al 2004). Therefore, diversity in the diet is important to meet the requirements for energy and other essential micronutrients.…”
Section: The Relationship Between Mean Adequacy Ratio (Mar) and Dietary Diversity Scoressupporting
confidence: 86%
“…Correlation coefficients (r) between DDS, NAR, and MAR of the 14 micronutrients were significant. This collaborate findings in earlier studies that diversity in the diet is positively associated with nutrient adequacy among women of reproductive age (Acham et al 2012;Arimond et al 2010;Drewnowski et al 1997;Foote et al 2004;Hjertholm et al 2019;Lee et al 2013;Mirmiran et al 2006;Nguyen et al 2018;Ogle et al 2001;Ruel 2003;Sultana et al 2019;Torheim et al 2003;Torheim et al 2004). Therefore, diversity in the diet is important to meet the requirements for energy and other essential micronutrients.…”
Section: The Relationship Between Mean Adequacy Ratio (Mar) and Dietary Diversity Scoressupporting
confidence: 86%
“…Although several studies reported MDD-W of Bangladeshi women, no studies prior to this one were found to include the dietary diversity of women from this island. The findings of the study indicate consensus with other studies focusing on MDD-W of Bangladeshi women which reported their low dietary diversity score (3.87 to 4.84) and a high percentage in the inadequacy of diversity (69%) [ 8 , 16 , 42 ]. Inadequately diversified diets among women of neighboring countries of Bangladesh, India (4.28 FG) [ 43 ], and Myanmar (4.09 FG) [ 44 ], are also reported in the literature.…”
Section: Discussionsupporting
confidence: 86%
“…Large and moderate improvements in DD over time could meaningfully decrease the risk of cognitive impairment, and conversely, worsening DD may increase the risk. This finding may be explained by the fact that DDS can be seen as a proxy and quick indicator of nutrient adequacy, and increasing the variety of food groups in the diet is positively associated with adequate nutritional intake [ 39 , 40 ], maintaining a higher DDS thus is associated with better cognitive function. In contrast, maintaining a lower DDS may mean malnutrition, which will increase the risk of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%